Rhein Induces Apoptosis in Human Breast Cancer Cells. (5th October 2011) - Chang, Ching-Yao; Chan, Hong-Lin; Lin, Hui-Yi; Way, Tzong-Der; Kao, Ming-Ching; Song, Ming-Zhang; Lin, Ying-Ju; Lin, Cheng-Wen
Abstract : Human breast cancers cells overexpressing HER2/ neu are more aggressive tumors with poor prognosis, and resistance to chemotherapy. This study investigates antiproliferation effects of anthraquinone derivatives of rhubarb root on human breast cancer cells. Of 7 anthraquinone derivatives, only rhein showed antiproliferative and apoptotic effects on both HER2-overexpressing MCF-7 (MCF-7/HER2) and control vector MCF-7 (MCF-7/VEC) cells. Rhein induced dose- and time-dependent manners increase in caspase-9-mediated apoptosis correlating with activation of ROS-mediated activation of NF- κ B- and p53-signaling pathways in both cell types. Therefore, this study highlighted rhein as processing anti-proliferative activity against HER2 overexpression or HER2-basal expression in breast cancer cells and playing important roles in apoptotic induction of human breast cancer cells.